2019
DOI: 10.1002/mde.3088
|View full text |Cite
|
Sign up to set email alerts
|

Where is the entrepreneurship bang for the patenting buck? Utility versus design patents

Abstract: This research contributes to the literature on entrepreneurship by studying whether design patents and utility patents have similar effects on entrepreneurial activity. Other contributions of this research include comparing the relative influences on startup versus established entrepreneurs and the effects of patents versus trademarks. Results, based on a panel of U.S. states, show that established entrepreneurs benefit from both types of patenting and from trademarks, whereas startup entrepreneurs significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…The literature has paid relatively little attention to the causes and effects of design innovations. This study focuses on the causes of design and utility patents, whereas some others have considered the effects of such patents (Goel & Saunoris, ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature has paid relatively little attention to the causes and effects of design innovations. This study focuses on the causes of design and utility patents, whereas some others have considered the effects of such patents (Goel & Saunoris, ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of entrepreneurship in fueling economic growth has dawned on policymakers worldwide, yet identification of factors that are key drivers of entrepreneurship is far from complete. Researchers have considered numerous influences on entrepreneurship (Acs & Audretsch, 2005; Cebula, Hall, Mixon, & Payne, 2015; Goel & Saunoris, 2018, 2020), and some studies have considered the impact of income inequality on entrepreneurship (Atems & Shand, 2018; Halvarsson, Korpi, & Wennberg, 2018; Ragoubi & El Harbi, 2018). Income inequalities have been persistent in many nations of the world, despite government redistribution efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Firms facing exit, through involuntary bankruptcy or those that are takeover targets, might abandon or slow their R&D spending, or refocus their R&D from innovation‐generation to imitation‐enhancement 10. The insignificant influence of R&D has been found in some other studies of firm exit (for instance, Bennett, 2019), although others have found that the type of innovation being pursued might matter (Goel & Saunoris, 2020). The other results generally supported the baseline findings.…”
Section: Resultsmentioning
confidence: 95%
“…Finally, R&D spending is included to determine if firms engaged in research were less likely to quit. The underlying idea is that firms engaging in research in the pursuit of innovation have an expectation of positive future payoffs and thus would be less likely to quit (see Goel & Saunoris, 2020). Next, we discuss the data employed and our estimation strategy to estimate Equation .…”
Section: Motivation and Modelmentioning
confidence: 99%